Strategi Pemasaran yang Digunakan di Minimarket Gea Mart di Kelurahan Sungai Rengas Kecamatan Maro Sebo Ulu - Syaputra, Aldi; Mubyarto, Novi; Hareastoma, Hareastoma (ARZUSIN, 2024)
This research discusses the marketing strategies used at the Geamart mini market in Simp Village. Rengas River District. Maro Sebo Ulu District. Batanghari, the aim of this research is to focus more on marketing so that consumers know about what the Geamart Mini Market offers. The type of research used is qualitative descriptive research. Data collection techniques using interview guidelines, observation sheets and documentation whose validity has been tested. The research subject is the owner of the Gea Mart mini market. Based on the results of research conducted by researchers at the Gea Mart mini market, Simpang Sungai Rengas sub-district, Maro Sebo Ulu sub-district, this research shows that the marketing strategy implemented by the Gea Mart mini market, which includes product selection, pricing, distribution and promotion, has succeeded in increasing consistent sales volume. The implementation of the marketing mix (4P) strategy has proven to be effective in attracting customer interest, with the main advantages being affordable prices, strategic locations, and promotions using billboards and banners. However, this research also found several shortcomings, such as product cleanliness, price differences with other mini markets, limited space facilities, and lack of promotion via social media. Therefore, even though Geamart's marketing strategy is quite effective, there is still room for improvement to achieve more optimal results. It can be concluded that the Geamart mini market marketing strategy, which includes product, price, distribution and promotion, has succeeded in increasing sales. The main advantages of this strategy lie in affordable prices, strategic locations, and effective promotions. However, there are several shortcomings such as product cleanliness, prices that are not always competitive, limited space, and lack of promotion on social media. Even though it is effective, improvements are still needed to achieve more optimal results.